2023
DOI: 10.1101/2023.09.01.555811
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sirenian genomes illuminate the evolution of fully aquatic species within the mammalian superorder Afrotheria

Ran Tian,
Yaolei Zhang,
Hui Kang
et al.

Abstract: Sirenians of the diverse superorder Afrotheria were the first mammals to retransition from land to water and are the sole herbivorous marine mammals, but little is known about the underlying genomic changes. Here, we generated a chromosome-level dugong (Dugong dugon) genome. A comparison of our assembly and a recent West Indian manatee genome with other afrotherian genomes revealed possible molecular solutions to aquatic life by sirenians, including a shift in daily activity patterns (circadian clock) and tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 217 publications
(341 reference statements)
0
2
0
Order By: Relevance
“…Meanwhile, a recent study confirmed that this gene is also inactivated in the West Indian manatee and dugong. 45 It has been proved that the nociceptive neurons in KCNK18 -KO mice showed a decreased threshold for activation and the skin nociceptive C-fibres showed an enhanced activation by cold. Consequently, the cold sensitivity of the KCNK18 -KO mice was enhanced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, a recent study confirmed that this gene is also inactivated in the West Indian manatee and dugong. 45 It has been proved that the nociceptive neurons in KCNK18 -KO mice showed a decreased threshold for activation and the skin nociceptive C-fibres showed an enhanced activation by cold. Consequently, the cold sensitivity of the KCNK18 -KO mice was enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the availability of resources for high-quality genome assembly in Afrotheria species remains limited, potentially obstructing the discovery of more nuanced evolutionary signatures within the Sirenia species. In the future, utilizing recently published high-quality dugong genomes, 45 , 48 we can delve deeper into the genetic basis of distinct adaptive evolutionary traits between manatees and dugongs, such as the tail fluke and skin morphology. Meanwhile, gene function verification experiments in vivo and in vitro should be further performed to validate the candidate genes we found in this study to be associated with the aquatic adaptive characteristics of the African manatee.…”
Section: Discussionmentioning
confidence: 99%